Web security for developers - McDonald, Malcolm (Computer programmer) (No Starch Press, Inc., 2020)
"Explores common attacks and vulnerabilities that web developers need to look out for. The first half of the book describes security concepts every developer should know ; the second half delves into individual vulnerabilities, such as SQL injection and cross-site scripting, offering real-world examples and code samples"--